Adipokines at the crossroad between obesity and cardiovascular disease - Molica, Filippo; Morel, Sandrine; Kwak, Brenda R.; Rohner-Jeanrenaud, Françoise; Steffens, Sabine (Thrombosis and Haemostasis, 2015)
Obesity, and especially excessive visceral adipose tissue accumulation, is considered as a low-grade inflammatory state that is responsible for adipocyte dysfunction and associated metabolic disorders. Adipose tissue displays endocrine functions by releasing pro- or antiinflammatory bioactive molecules named adipokines. An altered expression of these molecules, provoked by obesity or adipocyte dysregulation, contributes to major metabolic diseases such as insulin resistance and type 2 diabetes mellitus that are important risk factors for cardiovascular disease. However, obesity is also characterised by the expansion of perivascular adipose tissue that acts locally via diffusion of adipokines into the vascular wall. Local inflammation within blood vessels induced by adipokines contributes to the onset of endothelial dysfunction, atherosclerosis and thrombosis, but also to vascular remodelling and hypertension. A fast expansion of obesity is expected in the near future, which will rapidly increase the incidence of these cardiovascular diseases. The focus of this review is to summarise the link between metabolic and cardiovascular disease and discuss current treatment approaches, limitations and future perspectives for more targeted therapies.
Keywords: Obesity; adipokines; cardiovascular disease